An Effect of Contrast and Luminance on Visual Representational Momentum for Location. (August 2014) - Hubbard, Timothy L; Ruppel, Susan E
Effects of the contrast of target luminance and background luminance, and of the absolute level of target luminance, on representational momentum for the remembered final location of a previously viewed moving target were examined. Targets were high in contrast or luminance, decreasing in contrast or luminance, increasing in contrast or luminance, or low in contrast or luminance; the background was black or white. Representational momentum for target location was larger if targets were high or increasing in contrast or luminance and smaller if targets were low or decreasing in contrast or luminance. Representational momentum for target location was larger if targets were presented on a white background than on a black background. Implications for theories of localization and for theories of representational momentum are discussed.